A Flourishing Practice? - Toon, Peter (Royal College of General Practitioners (RCGP), 2014)
Peter Toon is the leading writer on primary care virtue ethics and this thought-provoking book builds on the thinking of philosopher Alasdair MacIntyre. A Flourishing Practice? looks at the moral problems that currently seem prevalent in health care. Common moral dilemmas highlighted by the media include threats to continuity of care, inappropriate care at the end of life, problems associated with commercialisation and privatisation of health care, defensiveness and risk aversion, and unrealistic expectations of care. The author argues that these all arise from a fundamental fragmentation of the value systems guiding our lives. The solution to these crises of professionalism and the pervading sense of moral crisis is the creation of a shared narrative. In this model of health care professionals and patients work together to cultivate the personal qualities that they need to flourish.